Welas Asih Diri dan Gejala Gangguan Makan: Infleksibilitas Psikologis sebagai Mediator - A'anisah, Rinda; Bintari, Dini Rahma (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Eating disorders are persistent problems related to eating behavior that can cause physical and psychosocial consequences. The increasing global prevalence of eating disorders underscores the need for an in-depth understanding of these disorders. It is known that the emergence of eating disorders is influenced by excessive evaluation one’s body and attempts to avoid unpleasant experiences. This indicates the role of psychological inflexibility in individuals with eating disorder symptoms. One of the protective factors against eating disorders is self-compassion, which is a gentle and loving attitude towards oneself, even when experiencing difficult experiences or emotions. Self-compassion helps individuals to become more flexible in dealing with their experiences and emotions, thereby avoiding maladaptive behavior. This study aims to examine the role of psychological inflexibility as a mediator in the relationship between self-compassion and eating disorder symptoms. This is a cross-sectional study involving 141 female participants aged 18-25 years (M=22,6, SD=2,02) who were obtained through convenience sampling techniques. Data retrieval is done using three measuring instruments, which are Self-compassion scale, acceptance and action questionnaire-II, and Eating Attitudes Test-13. The results showed that psychological inflexibility had a mediating effect in the relationship between self-compassion and eating disorder symptoms. Moreover, self-compassion cannot predict eating disorder symptoms directly without psychological inflexibility as an intermediary. It can be concluded that an individual's level of self-compassion lead to eating disorder symptoms through psychological inflexibility. The results also support the possible application of self-compassion interventions and acceptance and commitment therapy to treat eating disorder symptoms.